A Study of Grammatical Feature on Silsilah Ta`lim al-Lughah Al-`arabiyyah - Antoro, Asmakin; Thonthowi, Hamam (Program Studi Pendidikan Bahasa Arab, Fakultas Tarbiyah, IAIN Kediri, 2023)
This study aims to find out what nahwu materials are in the Silsilah Ta'lim al-Lughah al-'Arabiyyah book and also analyze the material that is in it and its relation to the title of the Arabic language material taught in it. This research is a type of qualitative research where the object of research is the book of Silsilah Ta'lim al-Lughah al-'Arabiyyah related to nahwu science. The book of Silsilah Ta'lim al-Lughah al-'Arabiyyah offers Arabic learning strategies by displaying nahwu rules, with the intention that the development of Arabic students is followed by good nahwu supervision. The author chooses to examine the book of Silsilah Ta'lim al-Lughah al-'Arabiyyah as a source of data in this writing, because there is nahwu which is used as a reference to achieve the target of success in learning Arabic.